PENGEMBANGAN KEMAMPUAN MAHASISWA DALAM TEKNOLOGI MUSIK MELALUI IMPLEMENTASI PEMBELAJARAN SOFTWARE DIGITAL AUDIO WORKSTATION - Fransiskus Rendy, B.Com, M.A.B, Fransiskus Rendy, B.Com, M.A.B (Akademi Komunikasi SAE Indonesia, 2022)
This research is expected to be able to decide the most common way to execute Sound Workstation computerized programming learning media in the Music Innovation course of the UNJ Music Expression Instruction Study Program. Furthermore, this exam is relied on to increase knowledge for teachers and students (students) see DAW programming as a computerized capability for 21st century music schools. This examination technique uses a subjective technique with an activity research approach (participatory activity research). This exam uses open meetings to analyze and understand the perspectives, perspectives, sentiments, and behaviors of people and study groups. Evaluate the feasibility and proficiency of running DAW programming in the assembly of melodic works. A consequence of the review shows that music innovation courses are organized to play an important role in coordinating innovation in schools. Then again, the use of innovation in learning exercises is complemented by the ultimate goal of working on the quality of training. Innovation can provide broad, fast, powerful and effective adoption of data dissemination across countries.